Education and training of healthcare staff in the knowledge, attitudes and skills needed to work effectively with breastfeeding women: a systematic review. Issue 1 (December 2016) - Gavine, Anna; MacGillivray, Steve; Renfrew, Mary; Siebelt, Lindsay; Haggi, Haggi; McFadden, Alison
Abstract Background Current evidence suggests that women need effective support to breastfeed, but many healthcare staff lack the necessary knowledge, attitudes and skills. There is therefore a need for breastfeeding education and training for healthcare staff. The primary aim of this review is to determine whether education and training programs for healthcare staff have an effect on their knowledge and attitudes about supporting breastfeeding women. The secondary aim of this review was to identify whether any differences in type of training or discipline of staff mattered. Methods A systematic search of the literature was conducted using the Cochrane Pregnancy and Childbirth Group's trial register. Randomised controlled trials comparing breastfeeding education and training for healthcare staff with no or usual training and education were included if they measured the impact on staff knowledge, attitudes or compliance with the Baby Friendly Hospital Initiative (BFHI). Results From the 1192 reports identified, four distinct studies were included. Three studies were two-arm cluster-randomised trials and one was a two-arm individual randomised trial. Of these, three contributed quantitative data from a total of 250 participants. Due to heterogeneity of outcome measures meta-analysis was not possible. Knowledge was included as an outcome in two studies and demonstrated small but significant positive effects. Attitudes towards breastfeeding was included as an outcome in two studies, however, results were inconsistent both in terms of how they were measured and the intervention effects. One study reported a small but significant positive effect on BFHI compliance. Study quality was generally deemed low with the majority of domains being judged as high or unclear risk of bias. Conclusions This review identified a lack of good evidence on breastfeeding education and training for healthcare staff. There is therefore a critical need for research to address breastfeeding education and training needs of multidisciplinary healthcare staff in different contexts through large, well-conducted RCTs.